Polymeric nanoparticles conjugate a novel heptapeptide as an epidermal growth factor receptor-active targeting ligand for doxorubicin - Liu CW (Dove Medical Press, 2012)
Chia Wen Liu,1,2 Wen Jen Lin11Graduate Institute of Pharmaceutical Sciences, College of Medicine, National Taiwan University, Taipei; 2Drug Delivery Department, Biomedical Engineering Research Laboratories, Industrial Technology Research Institute, Hsinchu, TaiwanBackground: This study was performed to develop a functional poly(D,L-lactide-co-glycolide)-poly(ethylene glycol) (PLGA-PEG)-bearing amino-active end group for peptide conjugation.Methods and results: PLGA was preactivated following by copolymerization with PEG diamine. The resulting amphiphilic PLGA-PEG copolymer bearing 97.0% of amino end groups had a critical micelle concentration of 3.0 × 10-8 mol/L, and the half-effective inhibition concentration (IC50) of the prepared PLGA-PEG nanoparticles was >100 mg/mL, which was much higher than that of PLGA nanoparticles (1.02 ± 0.37 mg/mL). The amphiphilic properties of PLGA-PEG spontaneously formed a core-shell conformation in the aqueous environment, and this special feature provided the amino group on the PEG chain scattered on the surface of PLGA-PEG nanoparticles for efficient peptide conjugation. The peptide-conjugated PLGA-PEG nanoparticles showed three-fold higher uptake than peptide-free PLGA-PEG nanoparticles in a SKOV3 cell line with high expression of epidermal growth factor receptor. Both peptide-conjugated and peptide-free PLGA-PEG nanoparticles were used as nanocarriers for delivery of doxorubicin. Although the rate of release of doxorubicin from both nanoparticles was similar, drug release at pH 4.0 (500 U lipase) was faster than at pH 7.4. The IC50 of doxorubicin-loaded peptide-conjugated PLGA-PEG nanoparticles in SKOV3 cells (0.05 ± 0.03 µg/mL) was much lower (by 62.4-fold) than that of peptide-free PLGA-PEG nanoparticles (3.12 ± 1.44 µg/mL).Conclusion: This in vivo biodistribution study in SKOV3 tumor-bearing mice was further promising in that accumulation of doxorubicin in tumor tissue was in the order of peptide-conjugated PLGA-PEG nanoparticles > peptide-free PLGA-PEG nanoparticles > doxorubicin solution.Keywords: amphiphilic copolymer, peptide, nanoparticles, SKOV3 cell, doxorubicin